Magnetic Hyperthermia with Magnetic Nanoparticles: A Status Review - Salunkhe, A.B.; Khot, V.M.; Pawar, S.H. (Current Topics in Medicinal Chemistry, 2014)
Recent advances in development of potential magnetic nanoparticles for magnetic fluid hyperthermia are summarized. This review covers relation between various size dependent physical properties and their applications subject to modification in synthesis methods. Brief discussion on different heating mechanism of magnetic nanoparticles is provided. This review covers recent progress of various magnetic nanoparticles including core shell type for in vitro, in vivo and pre-clinical trials. The highlight of this review is to build up a bridge between synthesis, surface modification and in vivo- pre-clinical in magnetic fluid hyperthermia.
Keywords: In vitro